MEMBANGUN KARAKTER TOLERANSI BERAGAMA SISWA SEKOLAH DASAR MELALUI LITERASI KEWARGAAN DI ERA MULTIKULTURAL - Ana Rahayu Lestari]; Jennyta Caturiasari; Nadiah Aulya Fathinah; Nurani Laraswati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the religious tolerance attitudes of elementary school students and to describe the role of citizenship literacy in shaping tolerant character in an era of multicultural society. The method used is a descriptive qualitative approach with data collection techniques through online surveys using Google Forms. The results show that although the majority of students have an attitude of respecting friends of different religions, there are still a portion of students who show negative responses, such as making religious differences a subject of jokes or mockery. Furthermore, the role of teachers in conveying values of tolerance is also not yet evenly distributed. These findings indicate the need for strengthening citizenship literacy in education, especially through contextual approaches that integrate the values of tolerance into students' everyday lives. Education that focuses on character and the values of diversity is expected to be able to shape an inclusive young generation that appreciates differences and is ready to become a tolerant global citizen.